Analisis Pergerakan Harga Saham Pada Sub Sektor Pertambangan Emas Sebelum dan Saat Adanya Pandemi COVID 19 - Erlin Afrianti; Jeni Susyanti; Khalikussabir Khalikussabir (E-JRM : Elektronik Jurnal Riset Manajemen, 2021)
AbstractThe purpose of the research is to find out the Analysis of Stock Price Behavior in Gold Mining Sector Sub-sector Before and During the Covid 19 Pandemic. The population in this study is 11 gold mining sector companies listed on the Indonesia Stock Exchange and the samples in the study are using purposive sampling techniques, so that it can be determined the number of samples as many as 4 Companies. Data collection method using secondary data, obtained by means of documentation by studying and analyze the stock history data of a company. Data analysis techniques used in this study test normality, and test t (t-test). The results stated that there is no difference in abnormal return and tranding volume of activity before and during the Covid-19 pandemic in gold mining sector companies.   Keywords: Abnormal Return, Tranding Volume Activity